2010
DOI: 10.1007/s12043-010-0167-8
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution by pupil plane phase filtering

Abstract: Resolution capability of any optical imaging system is limited by residual aberrations as well as diffraction effects. Overcoming this fundamental limit is called super-resolution. Several new paradigms for super-resolution in optical systems use 'a posteriori' digital image processing. In these ventures the three-dimensional point spread function (PSF) of the lens plays a key role in image acquisition. A straightforward tailoring of the PSF can be performed by appropriate pupil plane filtering. With a brief r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Also, formation of merit function should correctly reflect goals of optimization so that one can aim for problem-specific useful solutions. The merit function used in our earlier reports [38,39] did not directly incorporate provisions for setting desired targets for width of the central lobe and required field size. Few analytical studies, reported earlier, formulate the problem as a search for the pupil function in accordance with prespecified location for zeros in the point spread function.…”
Section: B Fitness Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, formation of merit function should correctly reflect goals of optimization so that one can aim for problem-specific useful solutions. The merit function used in our earlier reports [38,39] did not directly incorporate provisions for setting desired targets for width of the central lobe and required field size. Few analytical studies, reported earlier, formulate the problem as a search for the pupil function in accordance with prespecified location for zeros in the point spread function.…”
Section: B Fitness Functionmentioning
confidence: 99%
“…On the other hand, Liu and Wang used a constrained global optimization technique in the design of three-zone, phase-only, and amplitude-only optical pupil filters. We have reported earlier [38,39] our adaptation of evolutionary programming for the purpose, where we incorporated dynamic merit function to overcome stagnation problems in the optimization procedure, but the study was restricted to the case of equal area zones.…”
Section: Introductionmentioning
confidence: 99%
“…Optical aberrations reduce the overall performance of an optical system [30,31]. Aberrations can be reduced by using an optical element with a high optical transmission function [32][33][34][35][36][37][38][39][40][41][42]. Traditionally, apodization of the exit pupil of the optical system has been aimed at producing a high-quality output or increasing imaging qualities.…”
Section: Introductionmentioning
confidence: 99%